METODE PENGAJARAN YANG DIGUNAKAN GURU DALAM PENGAJARAN ONLINE: METODE YANG DISARANKAN PASCA PANDEMI - Andi Julian; Oikurema Purwati; Syafi'ul Anam (Universitas Islam Negeri Alauddin Makassar, 2023)
Online classes has shifted from offline to online learning since the global spread of Covid-19. Education field is also affected because of the pandemic. As a result, teaching and learning process have moved from traditional method to internet-based method. Thus, this paper aims to find out teacher’s method to teach English in online learning. To this end, this case study explores teacher’s strategies to teach English through online learning and teacher’ perception on teaching methods based on the students’ perspective toward the teacher in one of junior high school in Indonesia. This study conducted to 1 English teacher and 2 students of junior high school as the research subject. Data was analyzed qualitatively. Data collection techniques in this research was interview. The findings imply that there are some teaching strategies such as using digital applications, assessing students’ work using digital portofolio and preparing additional material laptop, internet quota, and digital materials. Analysis of online teaching methods were based on teacher’s interview and perception from students’ perspective. The result indicated that teacher’s teaching methods in conducting online teaching has succeeded. It has proven from students’ perspectives toward their teacher in online teaching. They hepls students to have good atmosphere in online learning.